2021
DOI: 10.3233/bme-201134
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional properties of TiC, TiN and TiNC thin films deposited by radio frequency magnetron sputtering

Abstract: BACKGROUND: Titanium nitride (TiN), titanium carbide (TiC) and titanium carbonitride (TiNC) thin films show promising practical applications due to their photoelectric properties and corrosion behaviour. OBJECTIVE: In this work, we investigated the factors which may affect the optical properties and the corrosion behaviour of these coatings. METHODS: The titanium coatings were carried out by sputtering using the target of Ti6Al4V (purity 99.96%) with different N2, CH4 and Ar partial pressures. XRD, FTIR, Raman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…[54,55] The clear fingerprints of the N ¼ C ¼ N and C-N vibrations are the characteristic peaks at approximately 2020, 2100, and 2320 cm À1 . [54][55][56] The ATR spectra also show the characteristic signal of C-H vibration at approximately 2900 cm À1 , in agreement with the Raman spectra. A surprising result is the very small intensity of O-H and N-H bands at wavenumbers above 3000 cm À1 , although the characteristic peaks due to these bands are present in the Raman spectra (see above).…”
Section: Atr Spectroscopy Of the Photomodified Ti Surfacesupporting
confidence: 78%
“…[54,55] The clear fingerprints of the N ¼ C ¼ N and C-N vibrations are the characteristic peaks at approximately 2020, 2100, and 2320 cm À1 . [54][55][56] The ATR spectra also show the characteristic signal of C-H vibration at approximately 2900 cm À1 , in agreement with the Raman spectra. A surprising result is the very small intensity of O-H and N-H bands at wavenumbers above 3000 cm À1 , although the characteristic peaks due to these bands are present in the Raman spectra (see above).…”
Section: Atr Spectroscopy Of the Photomodified Ti Surfacesupporting
confidence: 78%
“…Consequently, this combination is now acknowledged as the optimal sputtering condition within the scope of this study. The areal capacitance value obtained in this study surpasses the findings reported in a recent publication on the TiC thin film deposited through sputtering for protective coating application (124.39 μF/cm 2 ) . Additionally, it shows a comparable value to sputtered films used in supercapacitor applications, with only 1 order of magnitude lower (1500 μF/cm 2 ) .…”
Section: Resultssupporting
confidence: 47%
“…The areal capacitance value obtained in this study surpasses the findings reported in a recent publication on the TiC thin film deposited through sputtering for protective coating application (124.39 μF/cm 2 ). 13 Additionally, it shows a comparable value to sputtered films used in supercapacitor applications, with only 1 order of magnitude lower (1500 μF/ cm 2 ). 26 This highlights its superior performance compared to the limited existing research in this field.…”
Section: Electrochemical Analysis 341 Effect Of Deposition Conditions...mentioning
confidence: 93%
See 1 more Smart Citation
“…[23] The Fourier transform infrared (FT-IR) spectrum (Figure 2b) shows a characteristic peak of TiN at 600 cm −1 , corresponding to the vibrational stretching mode of TiN. [24] For PVDF-HFP, there are two characteristic bands at 408 and 614 cm −1 , corresponding to the α-phase of PVDF-HFP. [22] Meanwhile, the peaks at 485 and 1174 cm −1 represent the rocking and bending vibrations of the CF 2 and CF 3 groups in PVDF-HFP, respectively.…”
Section: Resultsmentioning
confidence: 99%